ANTIMICROBIAL AND FREE RADICAL SCAVENGING ACTIVITY OF LEAF AND STEM EXTRACT OF LIMONIA ALATA WIGHT AND ARN. - S, Malathi; T, Sekar; S, Sujatha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present study, antioxidant activities leaves and stem of the petroleum, chloroform, acetone, and methanolic extracts from Limonia alata (L.). Leaf and stem were investigated by employing established in vitro studies. The leaves and bark are used for the fomentation of rheumatic pain; the dried fruit is useful in malignant and pestilent fevers and is used as an antidote for poisons, the folklore claim suggests that the leaf is showing wound healing property. L. alata is belonging to the family Rutaceae. Methods: The ability of the plant extract to act as hydrogen/electrons donor or scavenger of radicals was determined by in vitro antioxidant assays using 2,2-diphenyl-2-picryl-hydrazyl free radical (DPPH) scavenging, reducing power assay, superoxide radical (O2*−) scavenging activity, phosphomolybdenum assay, ferric reducing antioxidant power and metal chelating activity, was performed to know the antioxidant potency and antimicrobial studies of the plant extract of leaves and stem of L. alata. Result: Results are evaluated higher in leaves, stem and root of L. alata (L.) recorded total phenol (59.95±5.30). The present state of work was designed to evaluate the phytochemical, antioxidant as well as to screen the antimicrobial present in the plant extracts of L. alata. The plant L. alata petroleum ether extract of leaf showed greater IC50 for DPPH assay (154.8 μg/mL) and compare to another extract, higher reducing power activity stem in methanol (0.99EDTAE/100 g extract), better phosphomolybdenum reduction (0.512 mg/g extract) higher ferric reducing power (11542.3MmolFe(II)E/mg) extract and higher superoxide radical scavenging activity in leaf extract (332.13%). However, the better metal chelating ability was shown by the water extracts of the leaf (18.24 EDTAE/100 g) compared to other solvent extracts. Conclusion: The result indicates the antioxidant and antibacterial activity potential of L. alata.